2002
DOI: 10.1086/340595
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of Solar Flare–accelerated Protons and α‐Particles from γ‐Ray Line Measurements

Abstract: The energies and widths of γ-ray lines emitted by ambient nuclei excited by flare-accelerated protons and α particles provide information on the ions directionality and spectra, and on the characteristics of the interaction region. We have measured the energies and widths of strong lines from de-excitations of 12 C, 16 O, and 20 Ne in solar flares as a function of heliocentric angle. The line energies from all three nuclei exhibit ∼1% redshifts for flares at small heliocentric angles, but are not shifted near … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 17 publications
5
33
0
Order By: Relevance
“…Line width and redshift measurements of nuclear de-excitation lines of 12 C, 16 O, and 20 Ne as function of the heliocentric angle provide information on the ions directionality, but current measurements are compatible with both downward isotropic distributions as well as with distributions with significant pitchangle scattering (Share et al 2002). Anisotropic velocity distributions could also be detected by Ha line polarization (Karlicky & Henoux 2002), but have not yet been detected in the pre-RHESSI era.…”
Section: Particle Acceleration Gamma Rays and Hard X-raysmentioning
confidence: 73%
See 1 more Smart Citation
“…Line width and redshift measurements of nuclear de-excitation lines of 12 C, 16 O, and 20 Ne as function of the heliocentric angle provide information on the ions directionality, but current measurements are compatible with both downward isotropic distributions as well as with distributions with significant pitchangle scattering (Share et al 2002). Anisotropic velocity distributions could also be detected by Ha line polarization (Karlicky & Henoux 2002), but have not yet been detected in the pre-RHESSI era.…”
Section: Particle Acceleration Gamma Rays and Hard X-raysmentioning
confidence: 73%
“…1-2, covering modeling of the coronal nonpotential magnetic field Yan et al 2001), gamma-ray, hard X-ray, soft X-ray, and EUV observations (Share et al 2001;Masuda et al 2001;Fletcher & Hudson 2001;Aschwanden & Alexander 2001), radio type II, III, and IV emission (Reiner et al 2001;Chertok et al 2001;Wang et al 2001c;Caroubalos et al 2001;Maia et al 2001a;Manoharan et al 2001), the Earthdirected halo CME (Andrews 2001;Reiner et al 2001;Manoharan et al 2001), the solar energetic particles detected in interplanetary space (Maia et al 2001a;Mäkelä & Torsti 2001;Smith et al 2001a;Bieber et al 2002), the heliospheric shocks and magnetic clouds (Dryer et al 2001;Lepping et al 2001;Whang et al 2001), the interplanetary magnetic field (Raeder et al 2001;Chen et al 2001), the response of the Earth's ionosphere and geomagnetic field AraujoPradere & Fuller-Rowell 2001;Chen et al 2001), transatlantic geopotentials (Lanzerotti et al 2001), the ring current dynamics (Jordanova et al 2001;Brandt et al 2001), atmospheric drag on satellite orbits (Knowles et al 2001), and detection in the outer heliosphere (Burlaga et al 2001;Wang et al 2001a). The 14 July 2000 Bastille Day flare was characterized with a number of superlatives: It was the third largest proton event 110 MeV since 1976, but the energy in 11 MeV ions was found to be only about 1% of the energy in 120 keV electrons (Share et al 2001). It ranked with its GOES class X5.7 as the 33rd larges...…”
Section: Space Weather On Bastille Daymentioning
confidence: 99%
“…Observations of redshifted lines argue that the fast ion pitch-angle distribution is significantly anisotropic, consistent with precipitation of most ions into the photosphere (Share et al 2002;Smith et al 2003). An ion population self-contained via MHD turbulence would still exhibit some residual anisotropy (Kulsrud & Pearce 1969) but detailed discussion of the magnitude of this effect lies outside the scope of this paper.…”
Section: Conclusion and Discussionmentioning
confidence: 82%
“…In the absence of such a departure, we need to note that there are flares in which a significant fraction of observed γ-ray line production does indeed appear to take place in the corona (Barat et al 1994;Vestrand & Forrest 1993), but also strong arguments against a nearly isotropic, coronally trapped population in other flares (e.g. temporal behaviour apparently requiring rapid precipitation, Hua et al 1989; redshifted γ-ray lines indicative of significant anisotropy, Share et al 2002). The situation appears unclear at present, but we may say that a coronal, possibly warm target origin for γ-ray lines appears possible in at least some events, and thus that warm target effects may be important in interpreting γ-ray line fluxes from at least some events (see also Sect.…”
Section: Introductionmentioning
confidence: 99%
“…We call these features the 'narrow' nuclear component. For SMM flares Share et al (2002) have shown that these lines are redshifted from their laboratory energies for flares at small heliocentric angles but not at heliocentric angles near 73°and above. This is consistent with a downward isotropic particle distribution.…”
Section: Nuclear De-excitation Linesmentioning
confidence: 96%